A consumer perspective on managing the consequences of chain liability. Issue 4 (7th February 2022) - Hartmann, Julia; Forkmann, Sebastian; Benoit, Sabine; Henneberg, Stephan C.
Abstract: Consumers tend to hold a focal firm responsible for its suppliers' unsustainable practices (chain liability), suggesting that firms need effective responses that can mitigate negative consumer reactions. In applying psychological contract theory to investigate recovery efforts related to such chain liability, the current study addresses three broad focal firm responses: Do nothing, choose a nonsubstantive response that verbally clarifies its own and the supplier's roles in the incident, or substantively rectify the supplier's wrongdoing with sustainability‐focused responses, such as termination, monitoring or development. With a vignette‐based experiment, we examine consumer perceptions and behaviors in three stages: before the unsustainable supplier incident (pre‐incident), after the incident (post‐incident) and after the focal firm has responded (post‐response). A nonsubstantive, clarification response decreases consumers' purchase intentions; substantive focal firm activities increase purchase intentions, though not fully back to pre‐incident levels. For consumers, termination, monitoring and development seem like equally adequate responses. Although combining several substantive responses offers even greater effectiveness for recovering purchase intentions, it still falls short of reaching pre‐incident levels. Thus, our findings demonstrate the focal firm's capacity to address suppliers' unsustainable practices substantively and recover, at least partially, its damaged relationship with consumers.